Faktor-faktor Yang Mempengaruhi Terjadinya Flour Albus (Keputihan) Pada Remaja Putri di SMA PGRI Pekanbaru Tahun 2013 - Komariah Olfa, Elmia Kursani, Hastuti Marlina, (Jurnal Martenity and Neonatal, 2015)
Excessive vaginal discharge is the discharge from the birth canal or vagina. The incidence of vaginal discharge in women in the world reached 75%, while in Indonesia, women who experience vaginal discharge reaches 70%, including teenagers. This study aims to determine the factors that influence the occurrence of flour albus (white) in adolescent girls in high school in 2013 PGRI Pekanbaru. This type of research is a quantitative analytical research design is cross sectional. The subjects were students of class X and Class XI, amounting to 125 people. The sampling technique used was simple random sampling using a questionnaire form questionnaire. Based on the results of the study showed the majority of respondents had a normal flour albus as many as 119 (95.2%), respondents with a low level of knowledge of as many as 24 people (19.2%), respondents with a negative attitude as many as 46 people (36.8%), respondents who did not perform personal hygiene as many as 45 people (36.0%), and respondents who use douching as many as 45 people (36.0%). Based on the statistical test all variables obtained P value <É‘ (0.05), means that there is a significant relationship between knowledge, attitudes, personal hygiene and douching with the flour albus. Based on statistical tests OR values obtained the highest among the other variables are variables with the knowledge of the value of OR (95% CI) = 9.900 (1.696 to 57.778), meaning that respondents have a low level of knowledge of the potential 9,900 times normal in flour albus not compare respondents which has a high level of knowledge.